Computed Tomography Scan Missed Diagnosis of Perforated Duodenal Ulcer - Oluwatunbi Joy Oluwaseun (Nigerian Journal of Medicine)
The present study reports a unique case diagnosed clinically as an intra-abdominal mass query Gastrointestinal stromal tumour but autopsy findings were that of a perforated duodenal ulcer with chemical peritonitis. X-ray and computed tomography scan were reviewed separately by two different sets of radiological experts and were unrevealing of the classical air under the diaphragm. An assessment of intra-abdominal malignancy was made and the patient died while being worked up for biopsy. At autopsy, a benign perforated ulcer was seen which was also confirmed on histology. The patient died from septicaemia. This case report is unique in describing a great radiological diagnostic challenge and provides a learning point for clinicians. It is reported to lay emphasis on the need for an increase in doctor’s awareness of the potential of radiological misdiagnosis of perforated duodenal ulcer and to encourage a high index of suspicion.